2014
DOI: 10.2196/resprot.3071
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Clinical Decision Support Tool for Primary Health Care Management of Back Pain: Development and Mixed Methods Evaluation

Abstract: BackgroundMany patients with back pain do not receive health care in accordance with best practice recommendations. Implementation trials to address this issue have had limited success. Despite the known effectiveness of clinical decision support systems (CDSS), none of these are available for back pain management.ObjectiveThe objective of our study was to develop a Web-based CDSS to support Australian general practitioners (GPs) to diagnose and manage back pain according to guidelines.MethodsAsking a panel of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Clinicians are known to adopt clinical decision support systems judiciously depending on social and environmental factors 33,34 . Thus, optometrists' attitudes towards AI may vary depending on the specific circumstances in which it is being used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians are known to adopt clinical decision support systems judiciously depending on social and environmental factors 33,34 . Thus, optometrists' attitudes towards AI may vary depending on the specific circumstances in which it is being used.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians are known to adopt clinical decision support systems judiciously depending on social and environmental factors. 33 , 34 Thus, optometrists' attitudes towards AI may vary depending on the specific circumstances in which it is being used. Kawamoto et al 35 conducted a large systematic review of 70 randomised controlled trials evaluating clinical decision support systems, and identified the provision of recommendations at the time and location of decision‐making as one of four independent predictors of improved clinical practice ( p = 0.03), defined by patient outcomes or process measures.…”
Section: Discussionmentioning
confidence: 99%
“…The tool was developed in collaboration with the George Institute for Global Health and published online in 2012. [24]…”
Section: Methodsmentioning
confidence: 99%
“…This includes embedding STarT Back within the clinic management software or introducing a “tick box” within electronic patient records when psychosocial assessment and care has been provided. As has been noted with other online clinical aids, to increase uptake tools need to be integrated into existing systems and routine workflow [ 42 ]. This would also allow reliable recording of practice for future research.…”
Section: Discussionmentioning
confidence: 99%